ANALISIS DEBT FINANCING PADA PERUSAHAAN INTERNASIONAL DAN PERUSAHAAN DOMESTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nilmawati Nilmawati (Jurnal Keuangan dan Perbankan, 2009)
The purpose of the research was to analyze and find empirical evidence of theeffect of categories of companies (international and domestic) on the level of debt using in thelisted companies in Indonesian Stock Exchange by controlling variables such as: risk, profitability,size, tangible fixed asset, growth, and agency problem. Multiple linier regression and chowtest were used for instrument analysis. The results showed that firm category did not effect thelevel of debt using, and there were only 2 control variables (profitability and agency) affectingthe level of debt using.